(untitled) (Baghdad Science Journal, 2016)
A rapid, simple and sensitive spectrophotometric method for the determination of trace amounts of chromium is studied. The method is based on the interaction of chromium with indigo carmine dye in acidic medium and the presence of oxalates as a catalyst for interaction, and after studying the absorption spectrum of the solution resulting observed decrease in the intensity of the absorption. As happened (Bleaching) for color dye, this palace and directly proportional to the chromium (VI) amount was measured intensity of the absorption versus solution was figurehead at a wavelength of 610 nm. A plot of absorbance with chromium (VI) concentration gives a straight line indicating that Beer’s law has been obeyed over the range of 0.5 -70 µg /25 ml, i.e., 0.02- 2.8 ppm with a molar absorptivity of chromium (VI) 1.71? 104 l.mol-1.cm-1, Sandell’s sensitivity index of 0.0030 µg.cm-2 .The detection limit of chromium was (DL) 0.0012 µg.mL-1 and a relative standard deviation of ? (0.70 -1.86)% depended on the concentration level. The method is developed for the determination of chromium(III) and has been successfully applied to the determination of chromium in various water samples, Pharmaceutical preparations ,standard rock sample of (MRG-1).